The accuracy of magnifying narrow band imaging (ME-NBI) in distinguishing between cancerous and noncancerous gastric lesions: A meta-analysis. Issue 9 (March 2018) - Zhou, Fan; Wu, Liucheng; Huang, Mingwei; Jin, Qinwen; Qin, Yuzhou; Chen, Jiansi
Abstract: Background: Previous clinical trials have demonstrated the diagnostic accuracy of magnifying narrow-band (ME-NBI) for gastric cancerous lesions, but the results are inconsistent. The purpose of this meta-analysis is to investigate the accuracy of ME-NBI in distinguishing between cancerous and noncancerous gastric lesions. Methods: Systematic literature searches were conducted until October 2016 in PubMed, Embase by 2 independent reviewers. Meta-analysis was performed to calculate the pooled sensitivity, specificity. Two authors independently evaluated studies for inclusion, rated methodological quality, and abstracted relevant data. Meta-analytic method was used to construct summary receiver operating characteristic curves, and pooled sensitivity, specificity were calculated. Results: Nine studies enrolling 5398 lesions were included. The pooled sensitivity, specificity were 88% (95% confidence interval [CI]: 78–93%), 96% (95% CI: 91–98%), respectively. The area under the curve (AUC) was 0.97. There was a large heterogeneity between the included studies. Studies with lesions ⩽ 10 mm still had a high pooled sensitivity of 81% (95% CI: 73–90%) and specificity of 97% (95% CI: 95–100%). Studies which analyzed resected specimens had a sensitivity of 91% (95 CI: 82–99%) and specificity of 88% (95% CI: 83–94%), and studies which analyzed biopsied specimens had a sensitivity of 85% (95 CI: 74–96%) and specificity of 99% (95% CI: 98–99%). Conclusions: ME-NBI is highly accurate and consistent to distinguish between gastric cancerous and noncancerous lesions.